Dramatic reductions in water uptake observed in novel POSS nanocomposites based on anhydride-cured epoxy matrix resins. (September 2015) - Hamerton, Ian; Tang, Winnie; Anguita, Jose V.; Silva, S. Ravi P.
Graphical abstract: Abstract: A methylnadic anhydride-cured diglycidylether of bisphenol A, is prepared and characterised and a mono-epoxy POSS reagent added (0.5–4 wt-%) to produce a series of nanocomposites. Two reaction mechanisms are observed involving esterification at lower temperatures (60–180 °C) and etherification at temperatures above 180 °C. Using the Ozawa and Kissinger methods, the activation energy for the first reaction was found to be 87–90 kJ/mol and 122–124 kJ/mol for the second reaction. Incorporation of POSS into the epoxy-anhydride network increases the T g and cross-link density, indicating a more rigid network, but the values do not follow a trend based solely on POSS content. The char yield increases with POSS content with very little change in the degradation temperature. Incorporation of POSS (1 wt-%) can reduce the moisture uptake in the cured resin by ∼25% at 75% relative humidity. This is accompanied by a lower impact on glass transition temperature: the T g is reduced by 10 K at saturation, compared with 31 K for the unmodified epoxy.